2022
DOI: 10.3390/ijms23073657
|View full text |Cite
|
Sign up to set email alerts
|

Neglected Facts on Mycobacterium Avium Subspecies Paratuberculosis and Type 1 Diabetes

Abstract: Civilization factors are responsible for the increasing of human exposure to mycobacteria from environment, water, and food during the last few decades. Urbanization, lifestyle changes and new technologies in the animal and plant industry are involved in frequent contact of people with mycobacteria. Type 1 diabetes is a multifactorial polygenic disease; its origin is conditioned by the mutual interaction of genetic and other factors. The environmental factors and certain pathogenetic pathways are shared by som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 92 publications
(130 reference statements)
0
13
0
Order By: Relevance
“…For several decades, paratuberculosis and meat, milk, and cheese contamination from cattle, sheep, and goats have spread globally, and humans may be threatened. In addition, it might present alive MAP or decay products in pasteurized milk and infant formula ( Ozana et al., 2022 ). Some studies confirmed that the prevalence of MAP is relatively considerable in cattle, sheep, and goats in different parts of Iran despite no data about MAP prevalence in Golestan Province ( Sadati et al., 2012 ; Anzabi and Khaki, 2017 ; Sadeghi et al., 2020 ; Pourmahdi Borujeni et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For several decades, paratuberculosis and meat, milk, and cheese contamination from cattle, sheep, and goats have spread globally, and humans may be threatened. In addition, it might present alive MAP or decay products in pasteurized milk and infant formula ( Ozana et al., 2022 ). Some studies confirmed that the prevalence of MAP is relatively considerable in cattle, sheep, and goats in different parts of Iran despite no data about MAP prevalence in Golestan Province ( Sadati et al., 2012 ; Anzabi and Khaki, 2017 ; Sadeghi et al., 2020 ; Pourmahdi Borujeni et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In both clinical and subclinical forms of JD, animals can shed the bacteria through their feces. MAP can be present in pasteurized milk, infant formula, water, soil, meat, and domestic aerosols ( Ozana et al., 2022 ). Since this bacterium is resistant to pasteurization and chlorination, the main transmission routes are water, food, and especially dairy products ( Sechi and Dow, 2015 ; Ozana et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the heat-shock protein 65 of Mycobacterium avium subsp. paratuberculosis (Hsp65 MAP ) and of Mycobacterium tuberculosis (Hsp65 Mtb ) also share great similarity with the pancreatic GAD65 in an antigenic peptide region (QERLAKLAGGVAVIKA) (Naser et al 2013;Ozana et al 2022). Amino acid sequence similarity between a putative Streptococcus pneumoniae (the pneumococcus) glutamate decarboxylase A (GadA Spn ) and GAD65 has also been reported (García and López 1995).…”
Section: Introductionmentioning
confidence: 98%
“…Besides, the heat-shock protein 65 of Mycobacterium avium subsp. paratuberculosis (Hsp65 MAP ) and of Mycobacterium tuberculosis (Hsp65 Mtb ) also share great similarity with the pancreatic GAD65 in an antigenic peptide region (QERLAKLAGGVAVIKA) (Naser et al 2013 ; Ozana et al 2022 ). Amino acid sequence similarity between a putative Streptococcus pneumoniae (the pneumococcus) glutamate decarboxylase A (GadA Spn ) and GAD65 has also been reported (García and López 1995 ).…”
Section: Introductionmentioning
confidence: 99%